2010
DOI: 10.1002/adsc.201000189
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic, Asymmetric Vinylogous Mukaiyama Aldol Reactions of Pyrrole‐ and Furan‐Based Dienoxy Silanes: How the Diene Heteroatom Impacts Stereocontrol

Abstract: Denmarks chiral bisphosphoramide/silicon tetrachloride system performs as an excellent Lewis base-Lewis acid catalyst for the vinylogous Mukaiyama aldol reaction of pyrrole-and furan-based dienoxy silanes with aromatic and heteroaromatic aldehydes. This asymmetric methodology provides a powerful synthetic entry to a variety of d-hydroxylated g-butenolide-type frameworks with high efficiency and valuable margins of regio-, diastereo-, and enantioselectivity. Notably, the nature of the heteroatom within the viny… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 77 publications
0
31
0
Order By: Relevance
“…Lactams offer the possibility of reactivity tuning by choosing an appropriate protecting group at the nitrogen atom. Since initial experiments with unprotected pyrrolin-2-one were not promising the respective tert -butyloxycarbonyl (Boc) and 4-toluenesulfonyl (Ts) derivatives 18a and 18b were prepared [ 52 ]. In CH 2 Cl 2 as the solvent, the attempted addition reaction of N -methyl- N -((trimethylsilyl)methyl)aniline ( 5 ) turned out to be sluggish.…”
Section: Results and Dicussionmentioning
confidence: 99%
“…Lactams offer the possibility of reactivity tuning by choosing an appropriate protecting group at the nitrogen atom. Since initial experiments with unprotected pyrrolin-2-one were not promising the respective tert -butyloxycarbonyl (Boc) and 4-toluenesulfonyl (Ts) derivatives 18a and 18b were prepared [ 52 ]. In CH 2 Cl 2 as the solvent, the attempted addition reaction of N -methyl- N -((trimethylsilyl)methyl)aniline ( 5 ) turned out to be sluggish.…”
Section: Results and Dicussionmentioning
confidence: 99%
“…227,228 After an initial survey of a prototypical reaction between TBSOP 163 and benzaldehyde (90) in the presence of a set of several chiral metal-based catalysts, it was discovered that the previously disclosed Denmark bisphosphoramide/SiCl 4 couple 399 was a superior catalyst candidate, with the expected (5S,1 0 S)-configured vinylogous aldol product syn-517 obtained in high yield and outstanding levels of site-, diastereo-, and enantioselectivities (Scheme 95, eq 1).…”
Section: Scheme 80 Enantioselective Synthesis Of the Fragments 446 Amentioning
confidence: 97%
“…Following their longstanding experience in the use of the popular heterocyclic silyloxy dienes, in 2010 Curti, Zanardi, et al reported a study focused on the catalytic vinylogous aldol reaction of pyrrole- and furan-based silyl dienolates (the latter being already cited in section 5 ) with aromatic and heteroaromatic aldehydes. 344 After a preliminary screening of various metal-based catalyst systems, it was found that the bisphosphoramide L12 /SiCl 4 couple was the optimal catalyst system to promote and govern the VMAR between silyloxy pyrroles 842 and aldehydes 843 , producing the expected lactams 844 with high efficiency and stereocontrol ( Scheme 213 ). It is noteworthy that the study revealed that the nature of the heteroatom substituents in the silyloxy diene scaffolds heavily affected the stereochemical reaction outcome; that is, the syn -configured adducts syn- 844 were preferentially obtained with pyrroles bearing electron-withdrawing N -protecting groups (Boc, Ts, Cbz), while the use of dienes N -substituted with electron-donating groups (Bn, allyl, PMB) (as in the case of furans, vide supra) provided reversal of stereocontrol, giving rise to anti - 844 adducts, preferentially.…”
Section: Vinylogous Amides and Lactamsmentioning
confidence: 99%